583 Prognostic impact of serum inflammatory biomarkers combined with il-6 expression in cervical cancer patients. (14th December 2020) - Domenici, Lavinia; Garibaldi, Silvia; Perutelli, Alessandra; Tonacci, Alessandro; Bottone, Pietro; Muzii, Ludovico; Panici, Pierluigi Benedetti
Abstract : Introduction/Background: Increasing evidences demonstrated a crucial role of inflammation in inducing and promoting several cancers. Cancer-related inflammation is an essential process in malignant disease by stimulating tumour cells proliferation, invasion mechanisms, metastasis, neoangiogenesis and by activating pathways of apoptosis's resistance. Cells and mediators of inflammation (as cytokines) represent a major part of tumour milieu. Particularly, IL-6 has been linked with cervical cancer development and progression by inducing upregulation of vascular growth factors (as VEGF), by modulating apoptosis, by fostering platelet production, activation and aggregation. An elevated platelet to lymphocyte ratio (PLR) has been recognised as markers of inflammation and also linked to poor prognosis in several malignancies. The aim of the study was to evaluate prognostic impact of inflammatory biomarkers (high platelet count, PLR) in combination with IL-6 tumour expression in cervical cancer patients. Methodology: Between 2016 and 2019, 108 out of 159 patients with cervical cancer presented to the Department of Gynecological, Obstetrical and Urological Sciences of "Sapienza" University of Rome and to the Division of Obstetrics and Gynecology at Department of Experimental and Clinical Medicine, University of Pisa have been enrolled. Study project was made in collaboration with National Research Council of Italy, Institute of Clinical Physiology (CNR-IFC) of Pisa. Cut off level of pre-treatment platelet count and PLR were identified by using ROC curve. IL-6 tumoural and peri-tumoural expression was analysed and stratified as low and high (low expression: 0, +1; marked expression:+2, +3). Results: Median follow up duration was 30 months (range 16–44). Patients with higher platelet counts showed worse OS and DFS (OS p <0.001 and DFS p <0.001, respectively figure 1A ). Cumulative rates of OS and DFS in patients with lower PLR were higher than in patients with higher values of PLR (OS p <0.001 and DFS p = 0.032; figure 1B ). Survival analysis showed a better prognosis in patients with lower IL-6 tissutal expression (PFS p <0.001; OS p <0.001; figure 2 ). Patients' characteristics were stratified according to platelet count, PLR, and IL-6 tissutal expression then compared using Pearson's correlation. Significant correlations were observed between negative cervical cancer-related prognostic factors (advanced stage of disease, tumor size, high grading, positive LVSI, lymph nodes and parametrial involvement) and pro-inflammatory patient's status. Conclusion: Nowadays causal relationship between inflammation, innate immunity and cancer is more widely accepted; however, many of the molecular and cellular mechanisms mediating this relationship remain unresolved. Ongoing inflammatory response was associated with poor outcomes in cervical cancer patients. A higher pre-treatment platelet count and PLR value associated with higher IL-6 tumoral expression could be used to predict poor prognosis in cervical cancer patients. Further investigations about inflammatory markers in prognostic models could contribute in early cervical patients' stratification and consequent management. Disclosures: None.